Study on the protective effect of an innovative cow milk-based product against some human skin-bacterial pathogens - Carlo Cosentino; Hazem Salaheldin Elshafie; Cristiana Labella; Carmine D'Adamo; Giovanni Pecora; Mauro Musto; Rosanna Paolino; Ippolito Camele; Pierangelo Freschi (Journal of Biological Research, 2018)
There is a growing interest related to the possible use of some components of cow milk that behave as immunomodulators, exert biological activity, and have anti-inflammatory factors. The aims of the study were: i) to investigate the chemical composition and antioxidant activity of Podolian cow milk; ii) to test the efficacy of some hand soaps supplemented with different percentage of cow milk compared to placebo; iii) to evaluate the antibacterial activity of milk added to soap. Antioxidant activity of Podolian milk resulted in mean 97.03% and 52.09% utilizing 2,2’-azinobis 3-ethylbenzthiazoline-6-acid and 2,2-diphenyl-1-picrylhydrazyl methods, respectively. The efficacy test showed that the most effective soap was obtained adding 5% of Podolian milk. For this soap, total counting bacterial test evidenced the highest reduction of bacterial hand contamination assessed by 98%.